ПРОБЛЕМА СХОДИМОСТИ ИНТЕРВАЛЬНОГО МЕТОДА ОБРАТНОЙ МАТРИЦЫ ДЛЯ РАСЧЕТА УСТАНОВИВШИХСЯ РЕЖИМОВ ЭЛЕКТРОЭНЕРГЕТИЧЕСКИХ СИСТЕМ - Ибрагимов, А.А.; Хамроева, Д.Н.; Мамуров, Т.Т. (SCIENCE and SOCIETY, 2022)
The article discusses the iterative method of the inverse matrix for calculating the steady state modes of electric power systems under the conditions that the parameters of the network under consideration have an interval uncertainty. The issue of convergence of the proposed method in the space of interval complex numbers is investigated. The convergence estimate was obtained on the basis of the spectral radius of the interval matrix resulting from the created iterative scheme.